Highly efficient Fenton and enzyme-mimetic activities of NH2-MIL-88B(Fe) metal organic framework for methylene blue degradation - Jianchuan He (Nature Portfolio, 2018)
Abstract Here, we show that NH2-MIL-88B(Fe) can be used as a peroxidase-like catalyst for Fenton-like degradation of methylene blue (MB) in water. The iron-based NH2-MIL-88B(Fe) metal organic framework (MOF) was synthesized by a facile and rapid microwave heating method. It was characterized by scanning electron microscopy, Fourier transform infrared spectroscopy, powder X-ray diffraction, and the Brunauer–Emmett–Teller method. The NH2-MIL-88B(Fe) MOF possesses intrinsic oxidase-like and peroxidase-like activities. The reaction parameters that affect MB degradation were investigated, including the solution pH, NH2-MIL-88B(Fe) MOF and H2O2 concentrations, and temperature. The results show that the NH2-MIL-88B(Fe) MOF exhibits a wide working pH range (pH 3.0–11.0), temperature tolerance, and good recyclability for MB removal. Under the optimal conditions, complete removal of MB was achieved within 45 min. In addition, removal of MB was above 80% after five cycles, showing the good recyclability of NH2-MIL-88B(Fe). The NH2-MIL-88B(Fe) MOF has the features of easy preparation, high efficiency, and good recyclability for MB removal in a wide pH range. Electron spin resonance and fluorescence probe results suggest the involvement of hydroxyl radicals in MB degradation. These findings provide new insight into the application of high-efficient MOF-based Fenton-like catalysts for water purification.